2016
DOI: 10.1108/intr-02-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

Do online access panels need to adapt surveys for mobile devices?

Abstract: Purpose Despite the quick spread of the use of mobile devices in survey participation, there is still little knowledge about the potentialities and challenges that arise from this increase. The purpose of this paper is to study how respondents’ preferences drive their choice of a certain device when participating in surveys. Furthermore, this paper evaluates the tolerance of participants when specifically asked to use mobile devices and carry out other specific tasks, such as taking photographs. Design/metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
81
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 19 publications
13
81
0
1
Order By: Relevance
“…For example, something like 25-30% of online surveys in 2014 are being attempted by people using mobile devices; a large proportion of CATI interviews are being completed via mobile phones; there has been substantial growth in the use of mobiles with CAPI ('mCAPI'); and new versions of traditional research are being invented, for example mobile auto-ethnography (Poynter, Williams & York 2014). The figure of 25-30% is in accord with figures reporting on overall mobile internet usage in the general worldwide population, which is also about 25% (Revilla et al 2014).…”
Section: The Visible and The Less Visiblesupporting
confidence: 78%
“…For example, something like 25-30% of online surveys in 2014 are being attempted by people using mobile devices; a large proportion of CATI interviews are being completed via mobile phones; there has been substantial growth in the use of mobiles with CAPI ('mCAPI'); and new versions of traditional research are being invented, for example mobile auto-ethnography (Poynter, Williams & York 2014). The figure of 25-30% is in accord with figures reporting on overall mobile internet usage in the general worldwide population, which is also about 25% (Revilla et al 2014).…”
Section: The Visible and The Less Visiblesupporting
confidence: 78%
“…Peterson () found that in the US female participants, younger people, people of Black and Hispanic backgrounds and medical specialists were more likely to access surveys on smartphones than on PCs when compared to other groups. All studies discussed earlier which found significant associations between device used and age and between device used and gender observed the same direction of association: younger people, as would be expected, were more likely to use mobile devices, and older people were more likely to use PCs and laptops (Toepoel & Lugtig, ; de Bruijne & Wijnant, ; Bosnjak et al , ; Revilla et al , ; Peterson 2012), and female participants were more likely to use mobile devices than male participants (de Bruijne & Wijnant, ; Peterson, 2012; Revilla et al , ).…”
Section: Background and Literature Reviewmentioning
confidence: 82%
“…They found a significant effect of age on use of mobile devices in surveys only in four countries out of seven (Brazil, Chile, Columbia and Spain) with older people being more likely to use PCs than mobile devices. Revilla et al () also reported a significant effect of number of people in the household on the use of a specific device in Portugal and Argentina with respondents from households with more people being less likely to use PCs. Peterson () found that in the US female participants, younger people, people of Black and Hispanic backgrounds and medical specialists were more likely to access surveys on smartphones than on PCs when compared to other groups.…”
Section: Background and Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations